EVALUASI TRANSAKSI MUDHARABAH BERBASIS PENDAPAT ULAMA SYAFI'YAH: KASUS PADA BANK SYARIAH X - Wahyu Dewi Hapsari; Slamet Sugiri Sodikin (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2017)
Bank Sharia X, located in certain city in the province of central Java, is one of branches of Bank Muamalat Indonesia. As the name implies, Bank Sharia X operates its business based on Islamic rules (Al-Quran and Al-Hadist). In interpreting the Al-Qur’an and Al-Hadist, Islamic scholars have different opinions on requirements of some specific topics, such as those on mudharaba transaction. Among the great schools of thoughts are Syafiiya, Malikiya, Hanafiya, and Hanabila. We aim to identify whether or not Bank Sharia Xfully applies its mudharaba transaction based on Syafiiyas school of thought. We collect data by interviewing key persons of the bank and investigating important, corroborating documents out there. We analyze the data by comparing between the application of mudharaba transaction and the Shafees school of thought on the themudharaba transaction. Based on our analysis, we find that Bank Sharia X applies its mudharabatransaction based on the requirements of Shafees thought except on (a) ijab and qabul, and (b) time limitation.